Scope of the application of international standards for the stages of training - Applied study on training institutes and centers in Asir region- - Alammare, Abdullah Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to know the extent of applying international standards for the training process stages in training institutes and centers in the Asir region. The study followed the quantitative descriptive approach, and the questionnaire was used as a tool to collect information. The study concluded that there is an application of international standards standards The practical phases of training in training institutes and centers in the Asir region to a large degree, and also reached the absence of statistically significant differences between the opinions of the respondents on the extent of applying international standards standards for the training process stages in training institutes and centers in the Asir region attributed to Variables (gender- the period of operation of the institute/ center- the type of beneficiaries of the institute/ center), and the presence of statistically significant differences between the opinions of the respondents about the extent of applying international standards standards for the stages of the training process in training institutes and centers in the Asir region due to variables (years of experience- job title) The study recommended the need to focus on applying international standards standards in determining training needs before planning and implementing the training process, and practicing effectively evaluating the training process.
Keywords: international standards for training; training process